Status and progress in quantitative proteomic study of postharvest fruits and vegetables during commercial treatment - LIANG Ze; WANG Lei; YANG Mingyi; LUO Zisheng; XU Yanqun; LI Li (浙江大学学报. 农业与生命科学版)
The postharvest commercial treatment of fruits and vegetables involves a variety of physiological and biochemical reactions such as ripening and senescence processes. The qualitative and quantitative analysis of proteins by using high-throughput proteomics can identify important proteins and their functions in the ripening and senescence process of fruits and vegetables, so that in-depth studies can be conducted on the regulation mechanism of fruit ripening and senescence, stress resistance, allergy and the response to exogenous treatment. This paper reviewed the physiological and biochemical changes of fruits and vegetables and the molecular mechanism of regulation after harvest by quantitative proteomics, which provides the guiding significance for the preservation study of fruits and vegetables during postharvest commercial treatment.